THE IMPACT OF GREEN SKILLS MISMATCHES ON GREEN JOB CREATION: EVIDENCE FROM NORTH MACEDONIA (The South East European Journal of Economics and Business, 2026)
The green transition and the adoption of new green technologies impact all workers, necessitating upskilling and reskilling to remain relevant to the changing labour market. The dynamics of the green transition is determined by many factors including the required green skills and related skills mismatches. Hence, the aim of this paper is to assess the impact of green skills mismatches on green job creation in North Macedonia. The empirical analysis is based on a survey of a representative sample of 530 companies, randomly selected from all regions, economic activities and company sizes. The green job creation is assessed by estimating fractional logit regression. Besides the standard control variables, particular attention has been paid to the underskilling, overskilling, skills deficits, skills obsolescence and horizontal skills mismatches. The results reveal that the green jobs creation is considerably limited by the presence of underskilling and skills obsolescence, while horizontal skills mismatches are emphasized as a problem that weakens the short run planning of green jobs. Accordingly, we suggest policy measures in the fields of education and business cooperation aiming to overcome skill mismatches and accelerate the green transition.